Agricultura periurbana na comunidade Boa Esperança, Itacoatiara, Amazonas, Brasil - Santos, Ingrid Pinheiro (Brasil, 2024)
Peri-urban agriculture plays a crucial role in understanding and resolving complex challenges faced by developing urban areas. Peri-urban areas are regions of great importance at the interface between rural and urban, with unique characteristics and challenges that require an integrated and sustainable approach to planning and development. Considering this scenario, the general objective of this work is to analyze the practice of peri-urban agriculture in the Boa Esperança community, Itacoatiara/AM. To achieve this objective, specific objectives were outlined: Identify the socioeconomic profile related to Peri-Urban Agriculture in the Boa Esperança community; Understand the existing work process in the Boa Esperança community; and describe the Technical Assistance and Rural Extension – ATER services provided to the community. The research methodology used was a qualitative and quantitative approach. For data collection, a semi-structured interview in the form of a questionnaire and a technical visit were used. Research participants were chosen according to previously established inclusion criteria. The results revealed an aging population with a decrease in the property succession process, despite the equal presence of men and women in agriculture. The level is predominantly low or medium, with a minority with technical or higher education. Pluriactivity is common, reflecting the diversity of income sources in families. The absence of technical assistance causes difficulties for farmers who face challenges with pests and diseases, opting for alternative control methods.